JUNIOR HIGH SCHOOL SCIENCE TEACHERS' PERCEPTION AND ATTITUDE TOWARDS IMPROVISATION OF SCIENCE INSTRUCTIONAL RESOURCES IN GOMOA-EAST DISTRICT - Segu-Essel, Gifty (American Journal of Education and Practice, 2021)
Purpose: The study investigated the perception, and attitude of the JHS science teachers towards improvisation of science instructional resources. The study also looked at the challenges they face when improvising. Methodology: The study employed a descriptive research survey design to collect data from 150 JHS science Teachers, 10 head teachers and five circuit supervisors in the Gomoa East District of the Central Region of Ghana using simple random technique. A questionnaire was used to collect quantitative data on JHS science teachers' perception, attitude and problems towards improvisation. Interview schedule was also used to collect qualitative data on head teachers' and circuit supervisors' attitude and support given to their teachers during improvisation. Descriptive and inferential statistics were used to analyze the data. Quantitative data were computed into means, frequencies, percentages, standard deviations and inferential statistics. The qualitative data collected was transcribed and analysed using descriptive and thematic narrative approaches. Findings: The results of the study showed that JHS science teachers had a negative attitude towards improvisation of science instructional resources despite their positive perception. The male teachers had a better attitude towards improvisation of science instructional resources than the female teachers. Recommendations: The study recommended that, on-hand mini workshops should be organized for the science teachers in the Gomoa East District to improve their skills and strategies in improvisation of science instructional resources. Secondly, female teachers should be supported by their head teachers to improve their attitude towards the improvisation of science instructional resources. Finally, the District Directorate in collaboration with the heads of schools should put in place strategies to improve upon teachers' skills and techniques to enable them improvise instructional materials.